A prática do tai chi chuan para a saúde do idoso: revisão de literatura - Letícia Sanz Grugel (2011)
The process of population aging is a reality in contemporary societies around the world. Aging is accompanied by multiple losses that compromise the quality of life of elderly and may bring with it the loss of autonomy and dependence, so the elder becomes frail. One of the main recommendations to improve the quality of life and preserve the autonomy and independence is to practice physical activity. Tai Chi Chuan is a Chinese gymnastics modality and has stood as one activity from light to moderate-intensity of great popularity among the elderly population in the entire world. The practice of this exercise has been shown in elderly patients: balance improvement, promotion of postural stability, cardiovascular and respiratory functions improvement, reduction of pain and stress and cognition and quality of sleep improvements. It is benefic to postural control and flexibility while improving muscle strength and reducing the risk of falls in the elderly. The objective of this paper was to identify through a critical literature review the effects of the Tai Chi Chuan practice in the health of the elderly. All the data basis indexed in the Virtual Health Library and Pub Med have been consulted. The researches were carried on in 2010 and were restricted to scientific articles with complete text in English, Portuguese and Spanish, published in 2005 and after that, available in the those data basis. The following key words and their synonymous in all chosen languages registered in the Health Sciences Descriptors were used: elderly and tai chi. Eight papers were selected which used TCC in different styles, such as intervention in elderly subjects with age greater than or equal to 59 years old. From the analysis of the articles was possible, despite different cultures and results, to conclude that Tai Chi Chuan can be an enjoyable and affordable opportunity for maintaining a healthy lifestyle. However, further studies are needed about the effects of Tai Chi Chuan for the health of the elderly, and thus conclude how the variables associated which this type of activity, is able to provide in the positive effects of elderly persons life quality.